MAHDIISME DALAM HADIS-HADIS MAHDAWIYAH - Muhammad Rikza Muqtada (Jurnal Theologia, 2019)
This paper discusses the origins of Mahdiism (al-Mahdi al-Muntaẓar) that are constructed using the mahdawiyyah ḥadīth with the status of aḥad (single transmitter) and ḍa'īf (weak). Nevertheless, this belief (Mahdiism) has deep roots in the theological reason of Muslims. By the historical approach, the finding shows that Mahdiism has roots in millenarianism (belief of the saviors' presence) that had existed in pre-Islamic traditions, such as Jewish and Christian. The elementary form of Islamic millenarianism is the concept of prophethood, but when the prophethood concept was deemed finished, it continued into the concept of Mahdiism. The first emergence of Mahdiism is in line with the emergence of mahdawiyyah ḥadīth. The emergence context of the mahdawiyyah ḥadīth revolves around the power transition from the Umayyad dynasty to the Abbasid dynasty, which always involved Shiite followers as the political victims. The contact between Shiites with the Jewish former and Christian former during the conflict at that time influenced the style of Shiite theology, like as millenarianism. The Shi'ites propagate the presence of al-Mahdi, as the savior from descendants of the prophet (Ahl al-Bait) described through the mahdawiyyah hadiths. Among the narrators of mahdawiyyah ḥadīth are Jewish former (Ka'ab al-Aḥbar) and Christians former (Wahb b. Munabbih). They were the pioneers who incorporated the millenarianism into the Mahdiism.